Ultrasonography does not consistently detect parathyroid glands in healthy cats. Issue 6 (11th July 2018) - Woods, Sarah J.; Palm, Carrie; Sheley, Matt; Feldman, Edward C.; Pollard, Rachel E.
Abstract: Ultrasound is used to evaluate the parathyroid glands of several species but there are limited reports of its use in cats. With this prospective anatomic study, we hypothesized that ultrasound could identify two parathyroid glands as hypoechoic nodules associated with each thyroid lobe and that a normal size range could be established. Six cat cadavers were imaged with ultrasound and histopathology of the thyroid and parathyroid tissue was performed for comparison. In addition, clinically healthy adult cats were prospectively recruited and placed in Group 1 (2–6 years; n = 11) or Group 2 (7–13 years; n = 9). Ultrasound of the cervical region was performed using a 7–15 MHz linear transducer. Number, size, and location of all hypoechoic nodules within or immediately adjacent to the thyroid lobes were documented. Ultrasound identified between 0–6 hypoechoic nodules per thyroid lobe in cat cadavers and between 0–3 hypoechoic nodules per thyroid lobe in clinically healthy cats, which does not correlate with the normal anatomy. In conclusion, parathyroid glands were frequently not ultrasonographically observed or were not distinguishable from thyroid tissue and this problem was worse in older cats because of the prevalence of nodular thyroid lesions, which primarily included foci of adenomatous hyperplasia.